Younger and Older Adults’ Cognitive and Physical Functioning in a Virtual Reality Age Manipulation - Vahle, Nils M.; Tomasik, Martin J. (Frontiers in Aging, 2022)
OBJECTIVES. Age group stereotypes (AGS), especially those targeting old age, affect an individual’s behavior and long-term cognitive and physiological functioning. Conventional paradigms investigating the related mechanisms lack validity and stability. Our novel approach for the activation of self-relevant AGS uses a virtual reality (VR) ageing experience, measuring relevant effects on performance parameters. METHODS. In a between-subjects experimental design, young participants embodied either a younger or older avatar in a 3D virtual environment to capture the effects on physical (Study 1; N = 68) and cognitive performance (Study 2; N = 45). In Study 3 (N = 117), the paradigm was applied to older participants. RESULTS. For the younger participants, embodying older avatars was associated with declines in memory and physical performance when compared to the younger avatar age group. Furthermore, the manipulations’ main effects were moderated by negative explicit AGS that matched the respective performance domains. For the older participants, we found no significant performance differences in the two domains investigated. DISCUSSION. The experimental manipulation demonstrated an impact on relevant performance parameters on a motivational and strategic level, especially for strong performance-related AS, but for young participants only. Possible reasons and mechanisms for the differences in younger and older samples’ results are discussed.